Respuesta :
I wouldn't use subsitution because that could be messy
I'll use elimination
multiply first equation by 3 and 2nd by 5 and add them
9c-15d=51
20c+15d=65 +
29c+0d=116
29c=116
c=4
sub back
3c-5d=17
3(4)-5d=17
12-5d=17
-5d=5
d=-1
c=4
d=-1
I'll use elimination
multiply first equation by 3 and 2nd by 5 and add them
9c-15d=51
20c+15d=65 +
29c+0d=116
29c=116
c=4
sub back
3c-5d=17
3(4)-5d=17
12-5d=17
-5d=5
d=-1
c=4
d=-1
4(3c-5d=17)-3(4c+3d=13)
12c-20d-12c-9d=68-39
-29d=29
d=-1, now you can use either original equation to solve for c
3c-5(-1)=17
3c+5=17
3c=12
c=4
So c=4 and d= -1
12c-20d-12c-9d=68-39
-29d=29
d=-1, now you can use either original equation to solve for c
3c-5(-1)=17
3c+5=17
3c=12
c=4
So c=4 and d= -1